The importance of applying building plan approval for renovation and alteration works / Nurul Syahirra Ahamad Rosli - Ahamad Rosli, Nurul Syahirra (Faculty of Architecture, Planning and Surveying, 2015)
In Malaysia, all of the renovation and alteration works of the building needs the approval from the Local Authorities. The Municipal Council is responsible in control the renovation and alteration works. This dissertation is all about the study of the importance of applying building plan approval for renovation and alteration works. The first objective, to study the process of building plan approval for extension or alteration and the related guideline. Secondly, to investigate which part of the building plan approval processes that are considered difficult for extension or alteration works. Lastly, the objective of this study is to survey the opinion regarding the effectiveness of building approval process in applying the approval for extension or alteration. The method applied in this study is qualitative method where a set of structured questions was answered by the related respondents such as Municipal Council officers and Personal Submitting Person (PSP). Based on the answer obtained, the study of the importance of applying building plan approval for renovation and alteration works was clearly answered. The results of the study were stated the overall process of the building plan approval and its guideline. Besides, the results also mentioned about the most difficult part of the process and the opinion of respondents regarding to the effectiveness of the process.